Seeking the Quality of Life - Kanon, Anna; Błaszak, Maciej (Sensus Historiae, 2024)
The paper distinguishes and interprets seven psychological characteristics of a valuable life, based on evolutionary-cognitive criteria—the rules of efficient cognition and adaptive functions of three global cortical networks: salience, executive and default mode. A life characterized by quality is emotionally acceptable, neotenic, based on priorities, relationships, autonomy, and competencies, taking into account values, efficient body, and useful environment.